Implicit collaborative caching mechanism for differentiated caching - ZHANG Jiageng; GUO Lei; WANG Qi; SUO Zhihai (Tongxin xuebao, 2024)
Aiming at the problem of cache homogenization in the current information center network, an implicit collaborative caching mechanism for differentiated caching was proposed. By assigning different types of caching tasks to each node in the collaborative group, an implicit collaborative group was constructed to achieve differential caching between adjacent nodes. This not only solved the problem of cache homogenization, but also avoided the communication consumption commonly found in explicit collaborative caching strategies, thereby improving cache diversity, increasing request hit rates, and reducing cache replacement times.